Pengaruh Features dan Reliability Terhadap Minat Beli Produk Paket Kado Bayi Pada Instagram Djovalyn Baby Shoes - Maulidiyah, Thursina (PERFORMA, 2023)
Djovalyn is an online business that runs in baby equipment especially baby gift package. Since the beginning of selling in 2018, Djovalyn has never achieved turnover target that is planned. That thing indicates purchase intention of low consumer on Djovalyn product. The purpose of this research is to find out the effect of features (X1) and reliability (X2) as independent variables on purchase intention (Y) of baby gift package products in Djovalyn Baby Shoes Instagram. The population in this research is Surabaya people who know baby gift package product of Djovalyn Baby Shoes. The respondent criteria to be research sample is respondent who is at least 18 years old, domiciled in Surabaya, and knows baby product package of Djovalyn Baby Shoes with the total sample of 150 respondents. The quantitative method is chosen to be the method of this research. Data is obtained by distributing questionnaires to respondents who are selected to be samples and then the data is analyzed by using SPSS 22. Data analysis technique that is used in this research is multiple linear regression. The hypothesis is tested through F test and t test. The result of the research shows that features and reliability affect positive and significant on purchase intention of baby gift package product in Djovalyn Baby Shoes Instagram.